Voluntary risk disclosure and firm value creation: from the perspectives of the agency and signalling theories / Rina Fadhilah Ismail - Ismail, Rina Fadhilah (Institute of Graduate Studies, UiTM, 2015)
Managing the risks and uncertainties of businesses that operate in a volatile and complex market environment has attracted considerable attention among market participants. Such concerns are particularly related to how businesses deal with the occurrence of increased risks in their business operations. However, the concept of corporate risk reporting has never been the main focus of the Malaysian Code of Corporate Governance (MCCG) when the Code was first introduced in 2000. Even though, there were several effects of economic crisis in 2007 on to the public listed companies (PLC), risk reporting remains a voluntary exercise. One of the prominent characteristics of Malaysian PLCs relates to the highly concentrated ownership structure where companies are mostly owned either by family members and the government. It is expected that these PLCs may face some forms of governance conflicts from the perspectives of agency and signalling theories. Thus, this study aims to review and to examine risk reporting while there is also a tendency of “agency-signalling” conflict when reporting the risk and how it would influence the firm value creation. Specifically, this study adopts a quantitative investigation to capture the voluntary risk information in the annual reports of 233 PLCs, where the final sample involved a total of 656 firm-year observations over a four-year period. This study finds that the most fitting theory that could explain the variation in the choice of voluntary disclosure would be the Agency Theory. The voluntary risk disclosure indicates improvement during the post-financial crisis period (i.e. 2008- 2009) due to the efforts of the regulators in promoting corporate transparency and governance…